Análise dos movimentos de larga escala que afetam o escoamento da camada limite atmosférica - Stefanello, Michel Baptistella (2021)
In the present thesis, the role of non-turbulent processes on the atmospheric boundary layer (ABL) is studied from a numerical point of view and employing experimental micrometeorological data. The thesis is constituted of three articles. In the first one, the effect of stable stratification increase on the flow is investigated by performing direct numerical simulation (DNS) of Ekman layers. The aim is to analyze the propagation and intensification of nearsurface large-scale modes and characterize them as meandering flow. Such non-turbulent modes are described by employing spatial Eulerian autocorrelation functions (EAFs) and spectral analysis, as well as mean and turbulent flow quantities profiles. Simulations show that horizontal meandering characteristics are found in the near-wall region under strong stratification and does not require any external forcing (e.g., surface heterogeneities or local perturbations) to develop. In the second article, meandering occurrences were investigated by using field measurements collected in southern Brazil. Wave-like episodes were isolated employing the temporal EAF approach. The results obtained showed that meandering structures often occur during low-wind and stable regimes and influence the scalar field introducing large-scale contributions to vertical fluxes. Such contributions should be filtered to estimate the turbulent transport correctly and improve the surface energy budget closure. The third article explores the effects of a forced geophysical flow, namely “Vento Norte”, associated with the local terrain features in the ABL based on two years of field observations. Before being detected close to the surface, the phenomenon disturbs the local flow, generating submeso motions. During its life cycle, it advects warm and dry air mass in a robust way, which significantly impacts the meteorological fields from the turbulent point of view, mainly during nighttime periods. The thesis’ results highlight the effects of non-turbulent scales in the flow dynamics under intense stable stratification.